Biotechnology In Farming And Its Role In Achieving SDG 2 (International Journal of Environmental Sciences, 2025)
Biotechnology in farming presents a transformative opportunity to advance Sustainable Development Goal 2 (Zero Hunger) by improving agricultural productivity, enhancing crop resilience, and ensuring food security. This study explores the role of agricultural biotechnology—encompassing genetically modified organisms (GMOs), gene editing tools like CRISPR, and bio-based innovations—in addressing the challenges of food scarcity, climate change, and land degradation. It examines how biotechnology contributes to increased yields, pest and disease resistance, improved nutritional content, and reduced post-harvest losses. The research also investigates the barriers to adoption, including regulatory constraints, public perception, ethical debates, and access disparities among smallholder farmers. Through a review of existing literature, case studies, and policy analysis, the study evaluates the effectiveness of biotech solutions in promoting sustainable agriculture. It concludes that with supportive policies, equitable access, and proper safety measures, biotechnology can play a crucial role in transforming global food systems and accelerating progress toward achieving SDG 2.